Analisis Kemampuan Menulis Puisi Bebas pada Siswa Kelas V SD Negeri 79 Palembang - Septiani, Nilam; Syaflin, Sylvia Lara; Akbar, M. Taheri (Indonesian Research Journal on Education, 2022)
This study aims to determine the ability to write free poetry in fifth grade students of SD Negeri 79Palembang. The method used in this research is a descriptive qualitative method. The total number of students studied in this study amounted to 15 students. The collection technique in this research is Observation, Interview and Documentation in the form of writing free poetry for fifth grade elementary school students. The data analysis technique used is data reduction, data presentation, conclusion drawing and verification. Aspects assessed in this study include indicators of poetry writing, namely the suitability of the content with the theme, diction and imagery. The results of the study showed that the ability to write free poetry in fifth grade students was categorized as sufficient. This can be seen from the aspect of the assessment. Conformity of the content with the title theme, totaling 6 students who get a score of 3, 6 students who get a score of 2, and 3 students who get a score of 1. For the aspect of Diction assessment, there are 2 students who get a score of 3, 6 students who get a score of 2, and 7 students who get a score of 1. For the Citraan assessment aspect, 3 students who get a score of 3, 1 student who gets a score of 2, and 11 students who get a score of 1.